Analisis Faktor-Faktor yang Berhubungan dengan Pemilihan Tempat Persalinan Ibu di Wilayah Kerja Puskesmas Ambukha Kecamatan Lolofitu MOI Kabupaten Nias Barat Tahun 2024 - Gulo, Mery Kristinawati; Ginting, Daniel; Sirait, Asima; Manurung, Kesaktian; Sinaga, Janno (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Background: Maternal mortality remains a significant public health concern in Indonesia, where 19.3% of deliveries are still conducted outside healthcare facilities or without skilled birth attendants. The working area of Ambukha Public Health Centre (Puskesmas) has the lowest proportion of facility-based deliveries in the West Nias District (67% in 2023), indicating the need to analyse factors associated with delivery place choice. Objective: To identify factors related to the selection of delivery place among mothers in the working area of Ambukha Public Health Centre, Lolofitu Moi Subdistrict, West Nias District. Methods: This study employed an observational analytic design with a cross-sectional approach. The population consisted of all mothers who delivered within the Ambukha Public Health Centre area in 2023 (N=78), and samples were obtained using a total sampling approach. Data were collected using structured questionnaires and analysed using Chi-square tests and logistic regression. Results: Significant associations were found between the choice of delivery place and maternal knowledge (p=0.000; OR=2.267), maternal attitude (p=0.000; OR=4.250), national health insurance (JKN) membership (p=0.000; OR=5.333), access to healthcare facilities (p=0.000; OR=6.038), husband’s support (p=0.000; OR=4.250), perceived need factors (p=0.000; OR=3.333), as well as cultural beliefs (p=0.004; OR=2.473). Multivariate logistic regression identified maternal knowledge as the most influential factor in delivery place selection, as indicated by the most significant coefficient value (B = –4.204) and statistical significance (p=0.005). Conclusion: Maternal knowledge, attitude, JKN membership, access to healthcare facilities, husband’s support, perceived need, and cultural beliefs are significantly associated with the selection of delivery place. Efforts to increase facility-based delivery coverage in this area should prioritise improving maternal knowledge, followed by strengthening other supporting factors.